2020
DOI: 10.1177/1558866120927322
|View full text |Cite
|
Sign up to set email alerts
|

Campus Wellness Facility, Student Contentment and Health

Abstract: Many U.S. college campuses have ways in which users’ lives can be enriched through wellness efforts. Provision of wellness and recreational services through a state of the art or newly renovated recreation and wellness facility is one avenue. The primary goal of this study was to determine the level of campus recreation facility satisfaction and utilization outcomes among student users at a Midwestern U.S. institution. The Recreation Wellness Survey was designed and its items were successfully tested for relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The overall findings of this study are generally consistent with other studies (Hallmann et al, 2012;Ko & Pastore, 2005;Makubuya et al, 2020;Wilson & Millar, 2021). The program quality and the physical environment were all indicative of overall service quality for recreational sport programs (Ko & Pastore, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall findings of this study are generally consistent with other studies (Hallmann et al, 2012;Ko & Pastore, 2005;Makubuya et al, 2020;Wilson & Millar, 2021). The program quality and the physical environment were all indicative of overall service quality for recreational sport programs (Ko & Pastore, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The program quality and the physical environment were all indicative of overall service quality for recreational sport programs (Ko & Pastore, 2005). Scholars have found largely on aspects of the physical environment as key factors influencing perceptions of service quality, including characteristics of sport facilities such as aesthetics (Gallardo et al, 2009), and availability of fitness equipment (Makubuya et al, 2020). In addition, previous study has pointed out program factors that have influenced perceptions of service quality, including the types of programs offered (Hallmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ko and Pastore (2005) found that the quality of programs, social interactions, and the physical environment were all indicative of overall service quality for recreational sport programs. Scholars have focused largely on aspects of the physical environment as key factors influencing perceptions of service quality, including characteristics of sport facilities such as proximity (Deelen et al, 2016;Wicker et al, 2013), aesthetics (Gallardo et al, 2009), and availability of fitness equipment (Makubuya et al, 2020). Further, previous research has pointed to programmatic factors that have influenced perceptions of service quality, including the types of programs offered (Hallmann et al, 2012) and opportunities to socialize (Mokoena & Dhurup, 2017).…”
Section: Recreational Sport Service Qualitymentioning
confidence: 99%
“…Previous research has also revealed that participants experience greater personal development and student learning as a result of participation in intramural sport (Forrester, 2015;Huesman et al, 2009;Makubuya et al, 2020). Scholars suggest that participants are likely to experience social outcomes as evidenced by improved communication skills, respectful behavior, and expanding social networks (Cooper et al, 2012;Phipps et al, 2015;Sturts & Ross, 2013).…”
Section: Benefits Of Intramural Sport Participationmentioning
confidence: 99%
“…This is supported by Kim et al (2016) suggestion that students who participate in university sports are more likely to transfer skills and character traits such as integrity, commitment, and work ethics learned from sports into their career fields. More benefits associated with sports participation by university students include; improved physical fitness, high self-esteem, better academic performance, and enhanced mental and social development (Coenders et al, 2017;Diehl et al, 2018;Forrester, 2015;Henchy, 2013;Kampf & Teske, 2013;Khan et al, 2012;Kim et al, 2016;Makubuya et al, 2020Vasold, et al, 2019Yigiter & Bayazit, 2013;Zegre et al, 2020). Additionally, if sports participation is maintained, the benefits lead to good health and well-being of students throughout their life on campus and even after graduation (Henchy, 2013).…”
Section: Introductionmentioning
confidence: 99%